Development and Assessment of Enzyme Immunoassay for Platelet-derived Microparticles - Osumi, Kazuoki; Ozeki, Yasushi; Saito, Sonoko; Nagamura, Yoshie; Ito, Hideki; Kimura, Yukio; Ogura, Hiroshi; Nomura, Shosaku (Thrombosis and Haemostasis, 2001)
Platelet-derived microparticles (PMPs) are released from platelets through the platelet activation by high shear stress, collagen, or calcium ionophore (A23187). PMPs are observed in patients with acute myocardial infarction, thrombotic thrombocytopenic purpura, hemolytic uremic syndrome, heparin-induced thrombocytopenia and other thrombotic disorders, but the importance of circulating PMPs in the pathogenesis of these diseases is still debated. Numbers of PMPs are usually determined by flowcytometry (FCM), but easier and reproducible PMP assay systems are needed. To develop a better ELISA for PMPs, we used antibodies against the platelet antigens anti-GPIb (NNKY5-5), anti-GPIIb/IIIa (NNKY2-11, anti-CD41), anti-GPIX (KMP-9), and anti-CD9 (NNKY1-19). PMPs were detected with all combinations of these antibodies, but the ELISA having the highest and most specific absorbance was obtained with a combination of KMP-9 (capture antibody) and NNKY5-5 (detecting antibody). PMPs in blood samples were measured by ELISA and FCM. ELISA correlated with PMPs quantitated by FCM. By shaking ELISA plates during incubation, nonspecific binding of platelets was eliminated. The level of PMPs was not increased in diabetes mellitus, thrombotic thrombocytopenic purpura, anti-phospholipid syndrome, or sepsis. The concentration of PMP was elevated in hemolytic uremic syndrome. Activated PMPs were absorbed to 0.8 m filter, but circulating PMPs were not absorbed. These results suggest that activated PMPs are likely to adhere to leukocytes or endothelial cells at the activation site and that the circulating form of PMPs are likely to be a residue of activated PMPs. To detect only the activated form of PMPs, a new ELISA needs to be developed, and it will likely use a combination of antibodies that detect platelet activation markers such as P-selectin (CD62P) or activated GPIIb/IIIa.
Keywords: Platelet-derived microparticle; enzyme-linked immunosobent assay; anti-GPIb/IX antibody; flow cytometry; HUS